Pola Perilaku Pengunjung terhadap Penggunaan Fasilitas di Orasis Art Space Surabaya - Putra Bayu Sutjipto; Wendy Sunarya (Syntax Corporation Indonesia, 2024)
The application of behavioral concepts in the form of privacy, and public space is present at Orasis Art Space. The pattern of visitor distribution causes social interaction for visitors to do activities at Orasis Art Space. The pattern of visitor distribution has a great influence on the number of visitors and the quality of social interaction created in Orasis Art Space. This research aims to gain a deeper understanding of the various elements of interior design, from lighting, spatial layout, use of color, to the arrangement of artwork exhibitions, and how the combination of all these factors can create an atmosphere that influences visitors' perceptions, emotions, and interactions with the artworks on display. The methodology in this study uses a qualitative descriptive approach. The qualitative descriptive approach aims to describe the current situation with observation techniques and data collection methods using the Person Centered Mapping method, which is used to determine the activity patterns of a group of people in the tendency to spread patterns of social interaction and space utilization. or grouping their behavior in a certain situation, time and place. The results of this study are to describe the principles and characters of behavioral architecture, and identify the relationship between usage behavior and design in Orasis Art Space.